Breaking Bad News Training in the COVID-19 Era and Beyond. (July 2020) - Soosaipillai, Gehan; Archer, Stephanie; Ashrafian, Hutan; Darzi, Ara
COVID-19 has disrupted the status quo for healthcare education. As a result, redeployed doctors and nurses are caring for patients at the end of their lives and breaking bad news with little experience or training. This article aims to understand why redeployed doctors and nurses feel unprepared to break bad news through a content analysis of their training curricula. As digital learning has come to the forefront in health care education during this time, relevant digital resources for breaking bad news training are suggested.